Analisis Industri Retail Nasional - Handy Martinus (Humaniora, 2011)
Fast moving in retail industry is the latest trading industry in trading chain. The study is to identify the condition of retail industry in Indonesia. This uses normative juridical approach. The research material is gathered by literature or document review. The analysis for modern retail industry is conducted through qualitative, thus explaining law material gathered from library being selected, arranging systematically, and finally getting conclusion figured to answer problems related to the rules for monopoly and dysfunction business competition in retail industry. The study result showed that modern market, which so far having a good performance, will have challenges. One biggest challenge is the potential for slow-moving revenue growth as the effects of slow-moving economic caused by global crisis.